SPEECH PROCESSING — A Dynamic and Optimization-Oriented Approach - Deng, Li; O'Shaughnessy, Doug (Marcel Dekker Inc., 2003)
Li Deng and D. O'Shaughnessy: , Publisher: Marcel Dekker Inc., New York, NY., June 2003 (http://www.amazon.com/gp/product/0824740408) Table of Contents: http://www.amazon.com/gp/reader/0824740408/ref=sib_dp_bod_toc/002-8541730-1403255?ie=UTF8&p=S00L#